2010
DOI: 10.1016/j.toxicon.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Microcystins in South American aquatic ecosystems: Occurrence, toxicity and toxicological assays

Abstract: The acute poisoning of chronic renal patients during hemodialysis sessions in 1996 in Caruaru City (Pernambuco State, Brazil) stimulated an intensive search for the cause of this severe complication. This search culminated in the identification of microcystins (MC), hepatotoxic cyclic heptapeptides produced by cyanobacteria, as the causative agents. More than ten years later, additional research data provides us with a better understanding of the factors related to cyanobacterial bloom occurrence and productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 126 publications
0
35
0
12
Order By: Relevance
“…This increase was probably motivated by the two incidents that led to human fatalities in 1988 and 1996 (Teixeira et al, 1993;Domingos et al, 1999;Carmichael et al, 2001;Azevedo et al, 2002;Molica 2002). Few studies have been conducted in other countries such as Panama and Colombia (Bartram et al, 1999;Dorr et al, 2010).…”
Section: Patterns In Toxin Testing Across the Tropicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase was probably motivated by the two incidents that led to human fatalities in 1988 and 1996 (Teixeira et al, 1993;Domingos et al, 1999;Carmichael et al, 2001;Azevedo et al, 2002;Molica 2002). Few studies have been conducted in other countries such as Panama and Colombia (Bartram et al, 1999;Dorr et al, 2010).…”
Section: Patterns In Toxin Testing Across the Tropicsmentioning
confidence: 99%
“…Since that incident some studies have been carried out on several reservoirs in South and Central America documenting blooms and progenitor species (Díaz-Pardo et al, 1998;Lind and Davalos-Lind, 2002;Ramirez et al, 2002;Bittencourt-Oliveira et al, 2005;Frias et al, 2006;Merino-Ibarra et al, 2007;Berry and Lind, 2010;Vasconcelos et al, 2010;Rejmánková et al, 2011). A review by Dorr et al (2010) revealed that there has been increased cyanobacterial bloom occurrence in water bodies in South America requiring better methods for screening and testing of cyanobacterial toxins.…”
Section: Introductionmentioning
confidence: 99%
“…In South America, the events of toxic cyanobacterial blooms have been under estimated and poorly documented [20]. One of the most common genera reported in blooms is Microcystis, responsible for the intoxication of 131 people and 52 deaths in Caruaru city, Brazil [21], as well as blooms in other areas of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of cyanobacterial (especially Microcystis aeruginosa) blooms caused by eutrophication have been a worldwide threat to aquatic ecosystems and human health (Dörr et al, 2010). Microcystins (MCs) are a family of monocyclic nonribosomal peptides produced by cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%